Buying And Selling Gold In A Non-Cash Perspective On Sharia (Analytic Study On Fatwa Of The National Sharia Council Number 77 Of 2010) - Muhammad Faqih Abdillah (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2023)
Buying and selling gold in cash is a form of gold sale and purchase agreement where payment is terminated and paid in installments within a predetermined timeframe. The current rapid economic growth has made so many Islamic banking institutions or other Islamic financial institutions offer gold installment products. Seeing the development of gold which always rises from year to year makes this business very tempting. At first glance there is no problem with buying and selling gold in cash, but in existing hadiths such as the hadith from Abu Sa'id al-Khudriy ra., and Ubadah bin Shamit ra., it is explained that it is not permissible to sell ribawi items with others. other ribawi items, except cash. It is also not permissible to sell it on credit, even though the two are of different types and sizes. But in the DSN-MUI fatwa No. 77/DSN-MUI/V/2010 concerning buying and selling gold in cash which was issued on June 3 2010, DSN-MUI states that buying and selling in cash is permissible (mubah), as long as gold does not become the official medium of exchange (money). ), either through ordinary buying and selling or buying and selling murabaha. It is interesting to study the reason for this fatwa being issued and the suitability of the legal advice of the DSN-MUI with the legal advice of the MUI in issuing this fatwa. In this study it can be concluded that: the reasons for the permissibility of buying and selling gold in cashless manner in the DSN-MUI fatwa No. 77/DSN-MUI/V/2010, DSN-MUI interprets the hadith of the Prophet SAW regarding buying and selling gold in a contemporary (contextual) way. This can be seen from the opinion of the DSN-MUI which states that gold and silver are goods (sil'ah) that are sold and bought like ordinary goods, and no longer saman (price, money). So that the result of the DSN-MUI's legal advice on buying and selling gold in cash is considered permissible (mubah).